Classer la vie : la taxinomie aux prises avec le corps dans le dossier médical de Bouvard et Pécuchet - Norioki Sugaya (Flaubert: Revue Critique et Génétique)
Taxonomy is certainly a fundamental discipline that is the basis of all rational sciences. In Bouvard et Pécuchet, we find the two men frequently trying to classify creatures and objects that however always elude their inventorial attempts. We will analyze the classification theme in Flaubert’s encyclopedic novel, in particular Chapter III devoted to the medical sciences. It is especially important to take into consideration the historical context of 19th-century medicine and examine the question of nosology, a medical discipline which studies the methodical classification of diseases. Our analysis of the aporias of knowledge will in fact reveal a certain conception of order and Nature, essential to Flaubert’s aesthetics.